Ответы и объяснения

  • Участник Знаний
2013-07-01T19:50:44+04:00

417

2X^2 + 3X - 2 = 0

D = 9 - 4*2*(-2) = 9 + 16 = 25

VD = 5

X1 = (-3+5)\4 = 2\4 = 1\2

X2 = -8\4 = - 2

418

3X^2 + 8X - 3 = 0

D = 64 -4*3*(-3) = 64+ 36=100

V D = 10

X1 = - 8 + 10 \ 6 = 2\6 = 1\3

X2 = -18\6 = - 3

419

-X^2 + 2X + 8 = 0

D = 4 - 4*(-1)*8 = 4 + 32 = 36

VD = 6

X1 = - 2 + 6 \ - 2 = 4\-2 = - 2

X2 = -8\-2 = + 4

420

-X^2 + 7X - 10 = 0

D = 49 - 4*(-1)*(-10) = 49-4*10 = 9

VD = 3

X1 = - 7 + 3 \ - 2 = -4\-2=+2

X2 = - 10\-2 = + 5

421

9X^2 -6X + 1 = 0

D = 36 - 36 = 0

X = 6 \ 18 = 1\3

422

4X^2 +4X + 1 = 0

D = 16 - 16*1 = 0

X = - 4 \ 8 = - 1\2

423

-X^2 +7X + 8 = 0

D = 49 - 4*(-1)*8 = 81

V D = 9

X1 = - 7 + 9 \ - 2 = 2\ -2= - 1

X2 = - 16\-2 = + 8

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

Лучший Ответ!
2013-07-01T21:16:58+04:00

№423

-x^2+7x+8=0    | * (-1)

x^2-7x-8=0

a=1 b=-7  c=-8

D=49-4*1*(-8)=49+32=81

\sqrt{81}=9 

x1=(7-9)/2=-1

x2=(7+9)/2=8

Ответ: -1; 8

№424

-х^2-2x+15=0     | * (-1)

x^2+2x-15=0

a=1   b=2   c=-15

D=4-4*1*(-15)=4+60=64

\sqrt{64}=8

x1=(-2+8)/2=3

x2=(-2-8)/2=-5

Ответ: 3; -5 

№425

5x^2-8x-4=0

a=5  b=-8  c=-4

D=64-4*5*(-4) = 64+80=144

\sqrt{144}=12

x1=(8-12)/10=-0.4

x2=(8+12)/10=2

Ответ: 2; -0,4

№426

6x^2-7x+1=0

a=6  b=-7  c=1

D=49-4*6*1=49-24=25

\sqrt{25}=5

x1=(7+5)/12=1

x2=(7-5)/12=\frac{1}{6}

Ответ: 1; \frac{1}{6}

№427

5x^2-8x+3=0

a=5  b=-8   c=3

D=64-4*5*3=64-60=4

\sqrt{4}=2

x1=(8+2)/10=1

x2=(8-2)/10=0.6

Ответ: 0,6; 1

№428

7x^2+9x+2=0

a=7  b=9   c=2

D=81-4*7*2=81-56=25

\sqrt{25}=5 

x1=(-9+5)/14=\frac{4}{14}=\frac{2}{7}

x2+(-9-5)/14=-1

Ответ: -1; \frac{2}{7}[/tex]